Molecular Biomarkers as Predictors of Treatment Response and Survival Outcomes in Head and Neck Squamous Cell Carcinoma: A Retrospective Cohort Study at a Singapore Tertiary Hospital - Lee, Martin Curtis; Nazilah Amir (Sriwijaya Journal of Otorhinolaryngology, 2024)
Introduction: Head and neck squamous cell carcinoma (HNSCC) is a heterogeneous disease with variable treatment responses. Identification of molecular biomarkers could personalize treatment and improve outcomes. Methods: A retrospective cohort study was conducted at a tertiary hospital in Singapore. Patients with HNSCC treated between 2018-2023 were included. Pretreatment tumor biopsies were analyzed for biomarker expression (PD-L1, EGFR, TP53, HPV status) using immunohistochemistry and PCR. Clinical data were collected from medical records. Treatment response, survival, and associations with biomarkers were analyzed. Results: 250 patients were included. PD-L1 expression was associated with improved response to immunotherapy (p = 0.02). EGFR overexpression correlated with worse overall survival (p = 0.01). TP53 mutations were linked to increased locoregional recurrence (p = 0.03). HPV-positive tumors had a better prognosis (p < 0.001). Conclusion: Molecular biomarkers show promise in predicting treatment response and survival in HNSCC. Integration of these markers into clinical practice could facilitate personalized treatment strategies.